Monkeypox Virus (MPXV) Infection: A Review - Kumari, Rosy; Arya, Pooja; Yadav, Surya P.; Mishra, Ratish Chandra; Parkash Yadav, Jaya (Infectious Disorders - Drug Targets, 2024)
Monkeypox is a viral disease; its outbreak was recently declared a global emergency by the World Health Organization. For the first time, a monkeypox virus (MPXV)-infected patient was found in India. Various researchers back-to-back tried to find the solution to this health emergency just after COVID-19. In this review, we discuss the current outbreak status of India, its transmission, virulence factors, symptoms, treatment, and the preventive guidelines generated by the Indian Health Ministry. We found that monkeypox virus (MPXV) disease is different from smallpox, and the age group between 30-40 years old is more prone to MPXV disease. We also found that, besides homosexuals, gays, bisexuals, and non-vegetarians, it also affects normal straight men and women who have no history of travel. Close contact should be avoided from rats, monkeys and sick people who are affected by monkeypox. To date, there are no monkeypox drugs, but Tecovirimat is more effective than other drugs that are used for other viral diseases like smallpox. Therefore, we need to develop an effective antiviral agent against the virulence factor of MXPV.
Keywords: virus